The influence of multiple variables on bipedal context in wild chimpanzees: implications for the evolution of bipedality in hominins - Sarringhaus, Lauren; Srivastava, Ryan; MacLatchy, Laura (Frontiers in Ecology and Evolution, 2024)
Investigations into the role of selection in the origin of human bipedalism using ape models have relied heavily on behavioral frequency data. However, analysis of video of wild apes has the advantage of capturing the details of the entirety of each rare, brief bipedal bout witnessed, not just the moment detected in observational studies. We used video to explore the behavioral context and effects of several variables on bipedalism across all ages in wild forest-dwelling chimpanzees from Ngogo, Uganda. We found, as in earlier studies, that adult chimpanzees used bipedalism in the context of foraging; however, unlike earlier studies, we found that while foraging was the predominant behavioral context during arboreal bipedalism, terrestrial bipedalism was more varied in contextual composition. We also found that these different behavioral contexts of bipedalism were associated with different variables. Specifically, foraging was associated with arboreality, hand assistance, and adulthood; antagonism was associated with adulthood, locomotion, and males; play was associated with terrestriality and subadulthood; and travel was associated with locomotion and females. Given that several variables influence bipedalism across multiple behavioral contexts in chimpanzees, it is likely that the early evolution of human bipedalism occurred under the influence of numerous factors. This exploratory study thus suggests that more comprehensive models should be used when reconstructing the transition to bipedalism from the Last Common Ancestor of humans and chimpanzees.